The Economic Viability of Agroforestry Practices in Increasing ‎Farmer Income and Land Productivity in Marginal Areas - Sulhan (International Journal of Accounting and Economics Studies, 2025)
This study explores the economic viability of agroforestry practices in enhancing farmer income and land productivity in marginal areas, ‎with a focus on Indonesia. Agroforestry systems, integrating trees with crops, are increasingly recognized as sustainable ‎solutions for improving soil fertility, reducing erosion, and providing diversified income sources for farmers in marginal lands. The study ‎reveals that agroforestry has led to significant improvements in farmer income, with increases of 27% to 35%, primarily due to additional ‎income from non-timber forest products (NTFPs). Moreover, agroforestry has been shown to enhance land productivity by improving soil ‎health and water retention, contributing to a 30% increase in crop yields. However, significant barriers, including high initial investment ‎costs and limited market access, hinder the widespread adoption of agroforestry. The study highlights the importance of institutional and ‎policy support, such as subsidies, training programs, and improved market access, in overcoming these barriers. The findings suggest that ‎agroforestry can be a viable solution for improving economic outcomes in marginal areas, but further policy interventions and research are ‎needed to facilitate its broader adoption‎.
Keywords: Agroforestry; Farmer Income; Land Productivity; Marginal Areas; Non-Timber Forest Products